White Papers and Revelations - Moltaji, Golbon (Université d'Ottawa | University of Ottawa, 2014)
Recruitment of international students theoretically prepares Canadian citizens, future ambassadors of Canadian trade and political interests for the global marketplace; appropriately, international students are now becoming an integral part of Canada’s immigration strategy. Contrary to the extensive options available to international students for permanent settlement in Canada, most of the programs in place are successful in attracting international students but not necessarily in retaining them.
Keywords: International Students; Immigration; Citizenship; Canada; Immigration Policy